2010
DOI: 10.1103/physrevd.82.035017
|View full text |Cite
|
Sign up to set email alerts
|

Flavor changingZcouplings at the LHC

Abstract: Models with a non-universal Z ′ exhibit in general flavor changing neutral currents (FCNC) at tree-level. When the Z ′ couplings favor the third generation, flavor changing transitions of the form Z ′ tc and Z ′ tu could be large enough to be observable at the LHC. In this paper we explore this possibility using the associated production of a single top-quark with the Z ′ and find that integrated luminosities of a few hundred fb −1 are necessary to probe the interesting region of parameter space.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Measurements of neutral K, D, and B meson mixing restrict couplings among the first two generations and the b quark to be quite small [41][42][43]. However, flavor-changing processes involving the top quark are relatively unconstrained by experiment, so that couplings such asūtZ may be substantial.…”
Section: Figmentioning
confidence: 99%
“…Measurements of neutral K, D, and B meson mixing restrict couplings among the first two generations and the b quark to be quite small [41][42][43]. However, flavor-changing processes involving the top quark are relatively unconstrained by experiment, so that couplings such asūtZ may be substantial.…”
Section: Figmentioning
confidence: 99%
“…The flavor changing Z has been also expected in theories with dynamical symmetry breaking approach. The top quark flavor changing have already been studied in many papers in the context of non-universality, where the strength of the couplings are different among different generations [21][22][23][24][25][26][27][28][29][30][31][32][33]. There are also beyond the SM theories where the flavor changing could proceed through color sextet vector and scalar bosons [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The models generating the observed Tevatron A t FB at tree level mainly fall into two categories: (i) s-channel exchange of vector mediators, the couplings of which to the top and the light quarks are axial and of opposite sign [11][12][13][14][15][16][17][18][19], 1 or (ii) t-channel exchange of flavor violating mediators such as new W 0 =Z 0 gauge bosons [21][22][23][24][25][26][27] or colored particles [28][29][30]. For various models of types (i) and (ii), comparative studies can be found in the literature [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%